On the use of timber structures in the actual construction in Vietnam - Doan, Định Kiến; Trinh, Văn Thưởng (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Timber, being a traditional construction material of Vietnam, is nearly not be utilised for structural construction in these recent years. Wood materials in Vietnam are very prosperous and diverse and have been experimented since the sixtieth years last century. Many types of timber structures were applied in constructions, mostly roof trusses and buiding frames by non-processed woods. Presently, the wood supply situation and processing capacity of our country know a great progress, apt for the applying of world wide advance timber structures. The paper will give an analysis of several appropriate advanced timber structures, specifically glued-laminated structures, and prefabricated metal connection details. Finally, some propositions on the actions to be performed for the appropriate utilisation and development of timber structures in Vietnam.